Modelagem de distribuição potencial e morfometria geométrica das populações florísticas de mangues no litoral sul de Sergipe, Brasil - Santos, Sindiany Suelen Caduda dos (2016)
Mangroves are heterogeneous, complex ecosystems and detainers o ecological, social and economic relevance. This argument evoked the investigation of the responses of the mangroves to the environmental variations as much in macroscale as in microscale. For this purpose, in general, the research investigated the action of the weather and of the relative sea level over the potential distribution of Avicennia L.; Laguncularia racemosa (L.) Gaertn f.; and Rhizophora mangle L., on the northern and northeastern brazilian coasts, in the time scale 6.000 before present, 2015 and 2050, as well as the phenotypic plasticity of the leaves of the mangroves of Real-Piauí-Fundo estuary complex, due to abiotic and anthropogenic factors that affect the floristic populations on the Southern coast of Sergipe, Brazil. The deductive method and the General Systems Theory have built the theoretical line for the research. On the analysis of the influence of climatic requirements and the influence on the relative sea level for the potential distribution of mangroves, the models generated from this tool of maximum entropy (MAXENT) showed variations of adequability areas in different scenarios. They also highlighted the influence of the annual temperature and the vertical distance to the nearest drainage as important variables on the predictions. From another point of view, to verify the occurrence of variations of shape and size on the leaves of the mangroves on the inferior, middle and superior estuaries of the Real-Piauí-Fundo estuary, in order to examine the phenotypic plasticity of the leaves, and which way the variation patterns are related to the sedimentological, climatic, and salinity of the water factors, samples of the flora, of sediment, of water, and of 450 leaves of A. schauerianna Stapf and Laechm, 600 leaves of Laguncularia racemose (L.) Gaertn f, and 600 for Rhizophora mangle. In the morphometric analysis, 3 anatomic marks and 16 anatomic semimarks were used on the previously digitalized leaf. The analyses revealed that both the leaf lamina and the size of the leaf showed significant variations among the three estuaries (p< 0.01). Then, even in microscale, tendencies of variation in shape and size of the leaves of the mangroves in the three sampling areas occur, submitted to various environmental pressures. With the purpose of evaluating the vulnerability of the mangroves of estuary complex, among anthropogenic tensors and the possible relation of these tensors with the phenotypic plasticity of the leaf, the methodology was created from systematic observations; from the fixation of attributes of anthropic tension; from the setting of weights for the group of anthropogenic tensors acting of mangroves; from the establishment of levels of vulnerability; and from the analyses of linear regression among shape, size and anthropic tensors. The sector with higher vulnerability is the superior estuary. But, all the areas are submitted to the risks of human actions. The results also showed that both the shape and the size of the leaves of A. schauerianna and R. mangle had significant values (p< 0.01), in contrast to L. racemosa. When concluding and making suggestions, the thesis indicates it´s possible to recreate the ecological history of the environments, to understand the phenomena of the present, both from the predictive modeling, and from the morphogeometric evaluations, and subsidize actions of the mangrove conservations, in order to avoid future losses of the mangrove flora.